Recognition of Changes in Air and Soil Temperatures at a Station Typical of China’s Subtropical Monsoon Region (1961–2018) - Ming-jin Zhan; Lingjun Xia; Longfei Zhan; Yuanhao Wang (Advances in Meteorology)
Trends in soil temperature are important but rarely reported indicators of climate change. Based on daily air and soil temperatures (depth: 0, 20, 80, and 320 cm) recorded at the Nanchang Weather Station (1961–2018), this study investigated the variation trend, abrupt changes, and years of anomalous annual and seasonal mean air and soil temperatures. The differences and relationships between annual air and soil temperatures were also analyzed. The results showed close correlations between air temperature and soil temperature at different depths. Annual and seasonal mean air and soil temperatures mainly displayed significant trends of increase over the past 58 years, although the rise of the mean air temperature and the mean soil temperature was asymmetric. The rates of increase in air temperature and soil temperature (depth: 0, 20, and 80 cm) were most obvious in spring; the most significant increase in soil temperature at the depth of 320 cm was in summer. Mean soil temperature displayed a decreasing trend with increasing soil depth in both spring and summer. Air temperature was lower than the soil temperature at depths of 0 and 20 cm but higher than the soil temperature at depths of 80 and 320 cm in spring and summer. Mean ground temperature had a rising trend with increasing soil depth in autumn and winter. Air temperature was lower than the soil temperature at all depths in autumn and winter. Years with anomalously low air temperature and soil temperature at depths of 0, 20, 80, and 320 cm were relatively consistent in winter. Years with anomalous air and soil temperatures (depths: 0, 20, and 80 cm) were generally consistent; however, the relationship between air temperature and soil temperature at 320 cm depth was less consistent. The findings provide a basis for understanding and assessing climate change impact on terrestrial ecosystems.